Efektivitas Kinerja Kader Pembangunan Manusia (KPM) dalam Percepatan Penurunan Stunting di Kelurahan Dadok Tunggul Hitam Kota Padang - Wijaya, Fauza; Yusran, Rahmadani (Jurnal Pemerintahan dan Politik, 2024)
This study aims to analyze the effectiveness of Human Development Cadres (KPM) in accelerating stunting reduction in Dadok Tunggul Hitam Village. Based on Article 11 paragraph (2) of Padang Mayor Regulation Number 80 of 2022 concerning the acceleration of stunting reduction in Padang City, the implementation of stunting reduction acceleration is carried out through the mobilization of KPM which is an active community that works to assist the village government in facilitating the local community related to planning, implementing, and supervising human resource development in the village. The method used in this study is descriptive qualitative, focusing on agencies, organizational devices, and communities who are involved in reducing stunting rates and at the same time becoming research informants. The results of this study indicate that the effectiveness of KPM performance in accelerating stunting reduction in Dadok Tunggul Hitam Village which is carried out through facilitating, advocating, and accompanying families is not yet effective. This is because KPM has not been able to mobilize the community to participate in socialization activities on healthy living behavior, the division of work areas is not yet even, has not succeeded in directing the community to register with the local DUKCAPIL, and KPM is often late in reporting and inputting stunting data. It is hoped that in the future, the Padang City Government will need to pay special attention to Human Development Cadres (KPM), especially in improving their abilities and understanding of problems in the field.